The Most Important Motor Coordination Skills in the Goalkeepers' Training - Andrzej Soroka (Lesya Ukrainka Volyn National University, 2018)
The conducted studies were aimed at identifying the most important coordination motor skills (CMS) among junior footballers playing as the goalkeepers as well as defining the impact of physical activity on young players' CMS. In this study there were used seven tests, which were able to asses in comprehensive and objective way seven most important CMS of football players. The studies were conducted with the participation of 26 goalkeepers form the Polish leagues of the first, second and third league, who played in junior teams in the 2015/2016 season. Statistica 10.1 PL program was used in statistical calculations as well as discriminative function analysis and one-way analysis of variance (ANOVA). The dominant CMS in young footballers playing as goalkeepers were: spatial orientation, coupled motion, adaptation and displacement of movement actions as well as, to a lesser extent, kinesthetic differentiation of movements. The highest level of CMS the goalkeepers achieved in the main part of training in the situation of the highest training load. It should be continued to monitor the level of CMS of goalkeepers, taking into account the type of exercise that focuses on developing particular motor skills.